Place, space, and geographical exposure: Foreign subsidiary survival in conflict zones - Dai, Li; Eden, Lorraine; Beamish, Paul W (Journal of International Business Studies, 2013)
This study focuses on the role of geography in foreign subsidiary survival in host countries afflicted by political conflict. We argue that survival is a function of exposure to conflicts, and depends on the characteristics of place (the conflict zone) and space (geographic concentration and dispersion of other home-country firms). The roles of place and space are explored using street-level analysis of geographic information systems data for 670 Japanese multinational enterprises (MNE) subsidiaries in 25 conflict-afflicted host countries over 1987–2006. Through dynamic modeling of conflict zones as stretchable and shrinkable places relative to subsidiary locations, we develop a means of characterizing a foreign subsidiary's exposure to multiple threats in its geographic domain. Our results show that greater exposure to geographically defined threats, in both a static and a dynamic sense, reduces the likelihood of MNE survival. The findings indicate, moreover, that both concentration and dispersion with other firms affect survival; however, the effects depend on where the firm is spatially located (whether the firm is in a conflict zone) and with whom (home-country peers or sister subsidiaries).